Pengaruh Pengeluaran Pemerintah, Investasi, dan Ketimpangan Pendapatan terhadap Pertumbuhan Ekonomi dan Kesempatan Kerja di Kabupatern Bone - Sudirman Sudirman; Asyraf Mustamin; Abdul Rahman; Bakri Bakri (Al-Buhuts, 2026)
This study aims to analyze the effects of government spending, investment, and income inequality on employment opportunities, with economic growth as an intervening variable. The study was conducted in Bone Regency using secondary data obtained from the Central Statistics Agency (BPS) for the period 2015–2022. The research design utilized quarterly time-series data, and the analysis was performed using Path Analysis with the assistance of SPSS version 26.The results show that government spending and investment have a positive and significant effect on economic growth, while income inequality has a positive but insignificant effect. Furthermore, government spending and investment were found to have a positive and significant effect on employment opportunities, whereas income inequality exerts a negative and significant effect. Economic growth was found to have a positive but insignificant effect on employment opportunities. Indirectly, government spending, investment, and income inequality have a significant effect on employment opportunities through economic growth as a mediating variable. Overall, these findings underscore the importance of effective fiscal policy, accelerated investment, and improved income equality in driving inclusive economic growth and expanding employment opportunities in Bone Regency. Although government spending and investment are capable of driving economic growth, this growth has not yet become an effective transmission mechanism for increasing employment opportunities at the regency level. These findings enrich the literature on regional economic development by emphasizing the importance of the quality of economic growth—not merely an increase in the growth rate—in driving the expansion of employment opportunities.